Coenzyme Q10-Polyethylene Glycol Monostearate Nanoparticles: An Injectable Water-Soluble Formulation - Kengo Banshoya; Tetsuya Nakamura; Tetsuro Tanaka; Yoshiharu Kaneo (MDPI AG, 2020)
Therapeutic applications of coenzyme Q10 (CoQ10) are greatly limited by its lack of solubility in aqueous media. In this study, polyethylene glycol monostearate (stPEG) was used to construct micelles containing CoQ10 as a new formulation. The micellar formulations (stPEG/CoQ10) were prepared using five types of stPEG with 10, 25, 40, 55, and 140 PEG repeat units, respectively. The micellar preparation was simple, consisting of only stPEG and CoQ10. Next, we compared the physical properties and blood circulation of these micelles. The CoQ10 load of this formulation was approximately 15 w/w%. Based on the dynamic light scattering method, the average molecular size of the stPEG/CoQ10 micelles was approximately 15 to 60 nm. The zeta potentials of these micelles were approximately −10 to −25 mV. The micelles using stPEG25, 40, and 55 demonstrated high solubility in water. Furthermore, these micelles had in vitro antioxidant activity. On comparing the blood circulation of micelles using stPEG25, 40, 55, and 140, micelles using stPEG55 had a significantly higher circulation in blood. The stPEG55/CoQ10 micelle demonstrated a protective effect against acetaminophen-induced liver injury in mice. In conclusion, these data indicate that the intravenous administration of the stPEG/CoQ10 micellar aqueous formulation is of great value against oxidant stress.